Is team-level injury analysis giving us the full story? Exploring a player-specific approach to analysing injuries - Bitchell, L.; Stiles, V. H.; Robinson, G.; Mathema, P.; Moore, I. S. (International Journal of Performance Analysis in Sport, 2024)
An examination of team-level and player-specific injury incidence in Rugby Union, using different match exposure calculations, Match time-loss injuries and match exposure using Global Positioning Systems (GPS) was collected across three seasons (2016/17-2018/19). Team-level and player-specific injury incidence were calculated using standard match length and GPS exposure. The probability of one or two or more injuries was calculated using the Poisson probability. A total of 487 injuries were sustained by 111 players. Team-level injury incidence across three seasons using standard match length was lower than the injury incidence using GPS (59.5 vs 95.7 injuries/1000 match hours, respectively). More than 84% of players fell outside the 95% confidence intervals for the team-level injury incidence each season. When exposed to a lower number of match hours, at the same incidence the probability of only one injury was higher. When exposed to a higher number of match hours, at the same incidence the probability of sustaining two or more injuries was higher. The standard match length underestimates the team-level injury incidence if the entire player cohort has not provided consent. In addition, team-level injury incidence is a poor representation of the underlying injury incidence of players.